A review of developmental factors of mentalization in childhood and adolescence - Gervinskaitė-Paulaitienė, Lina; Barkauskienė, Rasa (Psichologija, 2017)
The act of mentalisation refers to the capacity of understanding oneself and others in terms of intentional mental states (feelings, beliefs, intentions, and desires). Different definitions of this capacity for understanding mental states – such as theory of mind or reflective function – can be found in scientific literature along with subtle differences in conceptualisations of its development. Nevertheless, an increasing interest in interpersonal factors of development in mentalisation can be observed lately. One of the approaches in understanding the development of mentalisation is suggested by Fonagy and colleagues (1991, 2004), according to who the parent-child attachment and parental mentalisation are seen as key factors in the development of a mentalising capacity in children. Of these relationships, the ones in early development are discussed more widely. Much less is known theoretically and empirically about the relationships between parental mentalisation, a child’s attachment and mentalisation in middle childhood and adolescence. During these stages of development, important changes take place in the attachment system as well as within behaviors and needs of a child, including a move towards more integrated attachment representations together with socio-cognitive developmental changes related to puberty. It is not clear if parental mentalisation and a child’s attachment security remain of the same importance as they are in early childhood to the development and manifestation of child’s mentalisation from middle childhood to adolescence. Within this context, the aim of this paper is to analyse and reveal the most important empirical findings related to the research of mentalisation in childhood and adolescence. In this way, we aim to highlight and critically evaluate certain theoretical assumptions about the mentalisation of parents and a child’s attachment security as factors of a child’s mentalisation development. In this context, the aim of this paper is to analyze and to reveal the most important empirical findings related to the study of mentalisation in childhood and adolescence. An analysis of empirical studies showed that good parental mentalisation is important for attachment security and acquisition of theory of mind in early development. Data also reveals the importance of maternal reflective functioning for the development of organised attachment strategies. Moreover, poor maternal reflective functioning was related with disorganised attachment, which, according to different studies, was related to poorer mentalisation in early and in later development. Even though links between attachment security and mentalisation remain significant in middle childhood and adolescence, research findings indicate different relationships between strategies of attachment and mentalisation. It might be that not the attachment security itself, but the organisation of attachment representations might be an important condition for the development of mentalisation. Research findings show that maternal mentalisation remains important for the mentalisation of a child. On the other hand, there is still a lack of empirical data which could provide an opportunity to explain the mechanisms of how these processes interact in later development. An analysis of existing studies allows us to state that the approach-proposed development of mentalisation proposed by Fonagy and colleagues can partly be transferred to middle childhood and adolescence.
Keywords: mentalization; reflective function; theory of mind; early childhood; middle childhood; adolescence